Cone Beam Computed Tomography and Virtual Cloning: A Review - Sarkar, Anand Shankar; Hegde, Shruthi; Ajila, Vidya; Darwin, Deepthi (Journal of Health and Allied Sciences NU, 2023)
With the use of technologies, dental office workflow is moving toward a more efficient and cost-effective approach. Digitalization of dental records and computer-assisted imaging techniques have simplified workflow. Innovation and introduction of cone beam computed tomography, proface (facial three-dimensional [3D] soft-tissue capture), intraoral scan, planning software, and 3D printers has changed the dental profession. Clinical practice uses virtual workflows, and digital dentistry is a new development. The purpose of this article is to update the dental professionals with different available technologies for the creation of a virtual patient and digital tools that can be used for diagnosis, treatment planning, and follow-up of patients. The advantages of digital dentistry and future scope are highlighted in this article.
Keywords: intraoral scanners; facial scanning; virtual patient; digital dentistry; cone beam computed tomography